Regional Marketing to Change Regional Images: The Example of the Groningen Province Campaign - Pellenbarg, Pieter H.; Meester, Wilhelm J. (European Spatial Research and Policy, 2009)
An important element in the urban and regional development strategy of many local and regional governments is geographical marketing. The process of geographical marketing combines promotional, spatial and organisational activities, and can be aimed at various groups.From 1989 onwards, the province of Groningen, in the northern part of the Netherlands, has pursued such a geographical marketing campaign. This campaign, which is still being carried on, has used various means of communication: advertisements in newspapers and magazines, and radio and television commercials. It has been aimed at entrepreneurs and at the general public as well.An ex ante study of the public image of Groningen was carried out in 1988, before the start of the campaign. For this purpose, a random sample of the Dutch population was inquired by telephone. Since then, similar inquiries were carried out every 2 years, in order to measure the ‘effects’ of the campaign. In these inquiries, the image of the provinces of Friesland and Noord- Brabant (considered as ‘competitors’ in the place marketing arena) was measured along with that of Groningen, and used for reference. The data set now reaches up to the year 2005. The availability of this kind of data for a period of 17 years, measured at regular intervals, provides a unique opportunity to study the development of regional images through time, and to find suggestions for the best possible way to continue the marketing campaign.In this paper, the data of the inquiries will be analysed. The first question to be answered in the paper relates to the pace and the nature of the changes in image, observed in all three provinces. The second research question specifically deals with the influence of the marketing campaign on the image of Groningen.